PENGARUH ATRIBUT PRODUK TERHADAP MINAT MENABUNG NASABAH DI BANK SYARIAH - RONI ANDESPA (Universitas Islam Negeri Imam Bonjol Padang, 2018)
Research has the theme: Sharia Business Management. The research objective is: to examine the effect of product attributes on the interest in saving customers in Islamic banks. The research location is in West Sumatra Province, Indonesia. Research variables are: independent variables are product attributes (cost, function, location, information, image), and the dependent variable is interest in saving. The research population is all customers in Islamic banks operating in West Sumatra. The research sample was 250 customers. The research approach is a quantitative approach. The analytical tool used is multiple regression analysis. The results of the study are: product attributes have a significant influence on the customer's saving interest.